2009
DOI: 10.1371/journal.pone.0007258
|View full text |Cite
|
Sign up to set email alerts
|

Masitinib (AB1010), a Potent and Selective Tyrosine Kinase Inhibitor Targeting KIT

Abstract: BackgroundThe stem cell factor receptor, KIT, is a target for the treatment of cancer, mastocytosis, and inflammatory diseases. Here, we characterise the in vitro and in vivo profiles of masitinib (AB1010), a novel phenylaminothiazole-type tyrosine kinase inhibitor that targets KIT.Methodology/Principal Findings In vitro, masitinib had greater activity and selectivity against KIT than imatinib, inhibiting recombinant human wild-type KIT with an half inhibitory concentration (IC50) of 200±40 nM and blocking ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
321
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 365 publications
(328 citation statements)
references
References 31 publications
5
321
1
1
Order By: Relevance
“…49 However, the half-life of the drug is very short, and no durable and meaningful clinical responses were observed in clinical studies in AdvSM (Table 1). 50 Masitinib: Masitinib, which inhibits KIT WT and LYN, 51 is an effective drug for canine MC tumors. 52 However, in humans, the KIT D816V mutation introduces resistance against masitinib.…”
Section: Tyrosine Kinase Inhibitors (Tki)mentioning
confidence: 99%
“…49 However, the half-life of the drug is very short, and no durable and meaningful clinical responses were observed in clinical studies in AdvSM (Table 1). 50 Masitinib: Masitinib, which inhibits KIT WT and LYN, 51 is an effective drug for canine MC tumors. 52 However, in humans, the KIT D816V mutation introduces resistance against masitinib.…”
Section: Tyrosine Kinase Inhibitors (Tki)mentioning
confidence: 99%
“…3) Masatinib mesilate (AB1010) has been shown to inhibit human and murine KIT with juxtamembrane activating KIT mutations, as well as PDGFRA-a/b, and Lyn kinases at nanomolar concentrations in cell-based assays [122]. In contrast, masatinib only weakly inhibited KITD816V-driven cell proliferation (micromolar concentrations).…”
Section: Investigational Agentsmentioning
confidence: 99%
“…Dasatinib (Sprycel, Bristol-Myers Squibb, New York, NY, USA) , midostaurin (PKC412, Novartis) (Gleixner et al, 2006) and EXEL-0862 (Exelixis, San Francisco, CA, USA) (Pan et al, 2007) have been shown to inhibit D816V mutants, and clinical trials of midostaurin and dasatinib are currently going on in patients with aggressive SM and MC leukemia. In preclinical trials, masitinib (AB Science, Paris, France) proved to be the most specific inhibitor of c-Kit among TKIs (Dubreuil et al, 2009).…”
Section: Second Generation Tkismentioning
confidence: 99%